Effects of Physical Exercise on Sexual Function and Quality of Sexual Life Related to Menopausal Symptoms in Peri- and Postmenopausal Women: A Systematic Review. - Carcelén-Fraile, María del Carmen; Aíbar Almazán, Agustín; Martínez Amat, Antonio; Cruz Díaz, David; Díaz-Mohedo, Esther; Redecillas Peiró, Mª Teresa; Hita-Contreras, Fidel (MDPI, 2020)
During the menopausal period, sexual dysfunction is associated with the development or worsening of psychological conditions, causing deterioration in women’s mental health and quality of life. This systematic review aims to investigate the effects of different exercise programs on sexual function and quality of sexual life related to menopausal symptoms. With this purpose, a systematic literature search was conducted in PubMed, CINAHL, Scopus, Web of Science, and Cochrane Plus. A total of 1787 articles were identified in the initial search and 11 prospective studies (including 8 randomized controlled trials) were finally included. The most commonly recommended training programs are based on exercising pelvic floor muscles, as they seem to have the largest impact on sexual function. Mind–body disciplines also helped in managing menopausal symptoms. However, as far as the most traditional programs were concerned, aerobic exercises showed inconsistent results and resistance training did not seem to convey any benefits. Although positive effects have been found, evidence supporting physical exercise as a strategy to improve sexual function and quality of sexual life related to menopausal symptoms is limited, and further studies on this topic are needed.
Keywords: Menopausia; Mujeres - Conducta sexual; Ejercicio físico; Calidad de vida; Revisiones sistemáticas (Medicina); Sexual function; Physical exercise; Quality of life; Menopause; Systematic review